2019
DOI: 10.1111/1758-2229.12793
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of the cold adaptation ofPseudomonas putidaKT2440 and cold‐sensitive mutants

Abstract: Free-living bacteria such as Pseudomonas putida are frequently exposed to temperature shifts and nonoptimal growth conditions. We compared the transcriptome and metabolome of the cold adaptation of P. putida KT2440 and isogenic cold-sensitive transposon mutants carrying transposons in their cbrA, cbrB, pcnB, vacB, and bipA genes. Pseudomonas putida changes the mRNA expression of about 43% of all annotated open reading frames during this initial phase of cold adaptation, but only a small number of 6-93 genes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, CbrAB controls the expression of alginate biosynthetic genes and rsmA . It is also required to accumulate the sigma factor RpoS and core metabolites of aromatic and sugar metabolism [ 85 , 86 ]. Importantly, CbrAB and the master nitrogen regulator NtrBC directly control C/N homeostasis by regulating the transcription of histidine utilization genes ( hut ) [ 87 ].…”
Section: Rpon Is Required For Nutritional Metabolism and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CbrAB controls the expression of alginate biosynthetic genes and rsmA . It is also required to accumulate the sigma factor RpoS and core metabolites of aromatic and sugar metabolism [ 85 , 86 ]. Importantly, CbrAB and the master nitrogen regulator NtrBC directly control C/N homeostasis by regulating the transcription of histidine utilization genes ( hut ) [ 87 ].…”
Section: Rpon Is Required For Nutritional Metabolism and Growthmentioning
confidence: 99%
“…In succinate-depleted media, CbrAB activates hut transcription while derepressing the translation of hut mRNA mediated by the Crc/Hfq complex, which is sequestrated by the CbrAB-activated ncRNAs (CrcY and CrcZ). Interestingly, deletions of cbrA and cbrB impaired swimming and swarming motility, decreased T3SS-associated genes expression, and enhanced the sensitivity to cold [ 86 , 88 ]. This indicated that the RpoN/CbrAB–CrcYZ–Crc/Hfq regulatory cascade system controls more important phenotypes beyond carbon and nitrogen assimilation.…”
Section: Rpon Is Required For Nutritional Metabolism and Growthmentioning
confidence: 99%